2001
DOI: 10.1034/j.1399-5618.2001.030203.x
|View full text |Cite
|
Sign up to set email alerts
|

The prophylactic effect of long‐term lithium administration in bipolar patients entering treatment in the 1970s and 1980s

Abstract: A decrease in lithium prophylactic efficacy in consecutive decades was not observed. Small differences between the bipolar patients entering lithium therapy in the 2 decades were observed in terms of the previous history of illness and during the course of lithium administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 23 publications
1
53
0
9
Order By: Relevance
“…According to Grof, the responders have a characteristic clinical profile with an episodic clinical course, complete remissions, bipolar family history and low psychiatric comorbidity, approximating the classical Kraepelinian description of a manicdepressive illness. The percentage of excellent lithium responders among bipolar patients is about 30%, which has also been confirmed in the study by Rybakowski et al [9] where patients entering lithium therapy in the 1970s and 1980s were followed for a period of 10 years. However, the most exciting part of Grof's paper is an observation of the second generation of lithium-treated patients.…”
supporting
confidence: 64%
“…According to Grof, the responders have a characteristic clinical profile with an episodic clinical course, complete remissions, bipolar family history and low psychiatric comorbidity, approximating the classical Kraepelinian description of a manicdepressive illness. The percentage of excellent lithium responders among bipolar patients is about 30%, which has also been confirmed in the study by Rybakowski et al [9] where patients entering lithium therapy in the 1970s and 1980s were followed for a period of 10 years. However, the most exciting part of Grof's paper is an observation of the second generation of lithium-treated patients.…”
supporting
confidence: 64%
“…Their main advantage usually is the length of observation, in some instances reaching several decades 363, 364, 365. This comes at the cost of generalizability, in terms of both patient selection and non‐random treatment allocation.…”
Section: Maintenance Therapy For Bipolar Disordermentioning
confidence: 99%
“…Studies have shown that lithium is and remains highly effective for the treatment of classical bipolar disorder which dominated the original clinical trials [67,68] . In clinical trials with broadly diagnosed, heterogeneous bipolar spectrum disorders the efficacy of lithium has varied from low to impossible to demonstrate [69] .…”
Section: Clinical Profile Of Lithium Respondersmentioning
confidence: 99%